An Interview with Attorney General Michael Carpenter - Carpenter, Michael (Maine Policy Review, 1994)
In a recent interview with Maine Policy Review, Maine State Attorney General Michael Carpenter discussed the notable public policy challenges facing his office, specifically, and Maine law enforcement, generally.